The Exploration of Teacher’s Feedback and Students’ Perspective In Learning Writing English Text - Safrudin Sahmadan; Sariwati Muhamad (Peneliti.net, 2022)
This research was conducted based on the result of preliminary study that showed the unclear feedback given by the teacher which make the students incapable correct their writing. Furthermore, this research was carried out also based on the literature study that feedback is a debated issue among the second language acquisition (SLA) and (L2) writing researchers (Bitchener & Ferris, 2012; Ene & Kosobucki, 2016). This research aimed at investigated the kind of feedback given in learning writing process and the students’ perspective. The method used in this research was qualitative descriptive with apply the observation, questionnaire and interview as the instrument. The 20 students and 1 English teacher were engaged in this research as the subject. The data analysis technique use was interactive model comprise of data collection, data coding, data displayed and making conclusion or verification (Miles & Humberman, 1994). The result obtained appeared that the corrective feedback given was wittingly and directly, and it has giving a positive impact showed by 94% students state Very Happy and 6% students were state happy